Conversion of Military R&D
XIV, 296 p.
Keywords: The book describes the scale, benefits and costs of military research and development. It discusses the process of converting military R&D to civilian applications, and examines specific opportunities for, and obstacles to, conversion in the USA, Russia, France, Germany, and the UK. Among a number of case studies, senior scientists from US and Russian nuclear weapons laboratories debate the futures for these massive complexes. Looking to the future, the dual military/civilian nature of technology is discussed.